Analysis of Serum Uric Acid to Albumin Ratio in Acute Kidney Injury - Widiantara, Ade Kurniawan; Mangarengi, Fitriani; Widaningsih, Yuyun (INDONESIAN JOURNAL OF CLINICAL PATHOLOGY AND MEDICAL LABORATORY, 2025)
Hypoalbuminemia and hyperuricemia are associated with the occurrence of Acute Kidney Injury (AKI), leading to increased mortality. Epidemiological studies have shown that AKI is related to disease severity, mortality, period of stay in the intensive care unit, and prolonged use of mechanical ventilation. This study aimed to analyze the uric acid-albumin ratio in AKI. A retrospective cross-sectional study was conducted using secondary data from subjects diagnosed with AKI and treated at the Dr. Wahidin Sudirohusodo Hospital, Makassar for four and a half years from January 2019 to July 2023. Statistical analysis was performed using the Kruskal-Wallis, Mann-Whitney, and Receiver Operating Characteristic (ROC) tests. A total of 93 subjects with an average age of 56.4+15.6 were included in the study, with a higher percentage of males, 63.4% (59). The mean uric acid/albumin ratio was higher in AKI stage 3 = 3.17 compared to stages 1 and 2, with a significant value of p=0.866. The mean uric acid/albumin ratio was higher in AKI patients who died = 4.46, compared to those who recovered, with a significant value of p<0.001. There was a considerable correlation between uric acid/albumin ratio and outcome AKI (p<0.001) with strong correlation strength. Value uric acid/albumin comparison with AKI (p<0.001) strong category (r=0.842). Based on the ROC curve coordinate values uric acid/albumin ratio, a cut-off > 2.79 was obtained for the AKI who died and < 2.79 for the outcome AKI who recovered, with sensitivity of 97.7% and specificity of 91.6%. There was a significant correlation between the uric acid/albumin ratio and the outcome of AKI, with high correlation strength. However, no statistically significant correlation was found between the uric acid/albumin ratio and the AKI stage.